Set Kon Kim V. Officer In Charge, Cheras Police Station: Reflections On The Malaysian Law Of Extradition - Legislation and Judicial Decision - Hamzah, Wan Arfah (Journal of Malaysian and Comparative Law, 2019)
The decision of the High Court, Kuala Lumpur in Set Kon Kim v Officer In Charge, Cheras Police Station provides an opportunity to reflect on existing legislation governing extradition.